Olfactory communicatiaon : chemical characterization of the interdigital secretion of the black wildebeest, Connochaetes gnou - Slade, Desmond (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2000.